A Case Study Of Passive Piles Failure In Open Excavation - S. T. Kok (Deep Foundations Institute, 2009)
This paper presents a case study in West Malaysia for passive piles failure in very soft marine clay in open excavation. In this particular case, the thickness of the very soft marine clay ranges from 5 m to 7 m (16 ft to 23 ft) from the ground surface. Preliminary site investigation reported SPT ?N? value of zero for the very soft marine clay. The design was based on a deep foundation utilizing driven piles to support the superstructure. During pile cap construction, the piles were subjected to uncontrolled open excavation, inducing bending moment in the piles, resulting in some cracked and broken piles. Analyses were carried out using an existing three-dimensional finite element code with a non-linear soil model to predict the response of these piles during excavation. Finally, the predictions of pile responses during excavation were compared satisfactorily with the observed results.